Using Vertically Integrated Projects to embed research-based education for sustainable development in undergraduate curricula. Issue 8 (24th October 2019) - Strachan, Scott Munro; Marshall, Stephen; Murray, Paul; Coyle, Edward J.; Sonnenberg-Klein, Julia
Abstract : Purpose: This paper aims to share the University of Strathclyde's experience of embedding research-based education for sustainable development (RBESD) within its undergraduate curricula through the use of an innovative pedagogy called Vertically Integrated Projects (VIP), originated at Georgia Institute of Technology. Design/methodology/approach: This paper discusses how aligning VIP with the SDG framework presents a powerful means of combining both research-based education (RBE) and education for sustainable development (ESD), and in effect embedding RBESD in undergraduate curricula. Findings: The paper reports on the University of Strathclyde's practice and experience of establishing their VIP for Sustainable Development programme and presents a reflective account of the challenges faced in the programme implementation and those envisaged as the programme scales up across a higher education institution (HEI). Research limitations/implications: The paper is a reflective account of the specific challenges encountered at Strathclyde to date after a successful pilot, which was limited in its scale. While it is anticipated these challenges may resonate with other HEIs, there will also be some bespoke challenges that may not be discussed here. Practical implications: This paper offers a practical and scalable method of integrating SDG research and research-based education within undergraduate curricula. Social implications: The paper has the potential to deliver SDG-related impact in target communities by linking research-based teaching and learning with community outreach. Originality/value: The alignment of VIP with the SDG research area is novel, with no other FE institutions currently using this approach to embed SDG research-based teaching within their curricula. Furthermore, the interdisciplinary feature of the VIP programme, which is critical for SDG research, is a Strathclyde enhancement of the original model.